The Impact of Long-Term Abnormal Returns on Merger and Acquisition in US - YANG, JINHUA (2015)
In this paper, we are working on test the long term post-merger abnormal returns of firms in the market of United States of America. We used buy and hold abnormal return method to measure the long term abnormal return and used CAPM to confirm our results. The sample we used is list on the S&P 500 index and announced merger between 2000 and 2007. We found that the shareholders of the bidding firms earn an insignificant negative abnormal return in the long term and the form of payment has an influence on the long term stock performance (firms merged by cash indicate a better performance than firms merged by stock). In addition, we also tested the relationship between abnormal returns and book to market ratio and result shows both of them earn insignificant negative abnormal return while firms with high level of book to market ratio indicate a better performance.